Civic Education Teachers' Strategies in Managing Controversial Issues Amid Students' Digital Polarization - APRILLIO POPPY BELLADONNA; NENENG TRIPUSPITA; RIFQI ZAENI ACHMAD SYAM (Universitas PGRI Kanjuruhan Malang, 2026)
Digital polarisation resulting from social media use is increasingly influencing how students understand and discuss public issues, potentially hindering democratic dialogue in schools. This study aims to analyze the forms of digital polarisation experienced by students, identify the strategies employed by Civic Education (PKn) teachers when managing controversial issues, and examine the challenges involved in fostering inclusive discussions. A qualitative case study approach was employed at a high school in Bandung Regency, Indonesia. Data were collected through interviews, observations, and document analysis with three Civic Education teachers, twelve students, and one vice-principal responsible for student affairs. Data analysis was conducted using the Miles, Huberman, and Saldaña model. The results indicate that digital polarisation is characterized by selective exposure, confirmation bias, and a tendency to form homogeneous discussion groups that reinforce echo chambers. To address these issues, Civic Education teachers employed democratic dialogue, structured discussions, digital literacy, reflective questioning, and the integration of democratic values. The study proposes the Pedagogical Democratic Mediation Framework as a conceptual approach to strengthening students’ civic competencies and democratic participation.